Photothermal response and precise control of circularly polarized luminescence via double-layered films based on cholesteric liquid crystals - Huang, Sha; Wu, Qimei; Hu, Yongjie; Wang, Xincan; Yuan, Yongjie; Zhang, Hailiang (Journal of materials chemistry. C, Materials for optical and electronic devices, 2025)
The regulation of the performance of circularly polarized luminescence (CPL) materials has long been a subject of considerable interest. However, achieving simultaneous photothermal responsiveness and precise control of CPL performance remains a challenge. To address this issue, a double-layered film strategy is employed, where the overlap between the emission band of a luminescent layer, exhibiting non-polarized or circularly polarized luminescence, and the selective absorption and reflection bands of a cholesteric liquid crystal (N*-LC) layer with stimuli-responsive properties is utilized to achieve photothermal response and precise regulation of CPL performance. The non-chiral luminescent compound and the CPL copolymer are used as the first layer, combined with N*-LC polymers Azo( x )–Mt( y ) synthesized in this work, to prepare the double-layered films NI/Azo( x )–Mt( y ) and Py/Azo( x )–Mt( y ). Non-polarized or circularly polarized fluorescence is emitted from the first-layered film upon light excitation, allowing static regulation of CPL performance after passing through selective absorption and selective reflection of the second-layered N*-LC film. Additionally, the CPL signals of double-layered films are further precisely regulated in terms of on–off, inversion, intensity, and wavelength by adjusting the Azo( x )–Mt( y ) copolymer composition. Furthermore, under different photothermal conditions, the CPL wavelength and intensity of double-layered films are dynamically regulated by stimulating Azo( x )–Mt( y ), as azobenzene mesogens undergo trans – cis isomerization.